(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The author of the article reviews the idea of the development of knowledge integration in the works of great medieval Oriental scholars Al-Farabi, Al-Khwarizmi, and others. Concurrence of this process is presented through works of scholars in which mathematics is integrated with music, art, and architecture.